Granting Birthright Citizenship - A Door Opener for Immigrant Children's Educational Participation and Success? - Judith Saurer; Christina Felfe (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Does granting citizenship at birth help immigrant children to integrate in the host country's educational system and thus, to promote their educational success? Our identification strategy is based on a reform of the German naturalization law in 2000. We exploit this natural experiment and use a difference-in-difference design that compares children born shortly before and after the reform in years of policy change and years where no policy change took place. Our empirical analysis relies on two comprehensive datasets, administrative data from school entry examinations and the German Micro Census, Europe's largest household survey. We find positive effects on immigrant children's participation in non-mandatory preschool (by 3.2 percentage points) and referral to upper secondary school (by 7.8 percentage points).
Keywords: J15; J24; I21; 330